2017
DOI: 10.2134/jeq2016.10.0388
|View full text |Cite
|
Sign up to set email alerts
|

Biochars Reduce Mine Land Soil Bioavailable Metals

Abstract: Biochar has been proposed as an amendment to remediate mine land soils; however, it could be advantageous and novel if feedstocks local to mine land sites were used for biochar production. Two different feedstocks (pine beetle-killed lodgepole pine [Pinus contorta] and tamarisk [Tamarix spp.]), within close proximity to mine land-affected soils, were used to create biochars to determine if they have the potential to reduce metal bioavailability. Four different mine land soils, contaminated with various amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 39 publications
1
40
1
Order By: Relevance
“…Considering that recent work has demonstrated how higher pyrolysis temperatures produce biochars with greater metal sorption capacity (Rodríguez-Vila et al 2017), it may be that employing biochars produced at 550°C (which would have greater sorption capacity than those used in the present study) could overcome this theorised mobilisation effect. Hypotheses aside, the results appear comparable with those of Ippolito et al (2017) who observed varying degrees of success in reducing extractable Cd in mine contaminated soils treated with pine and tamarisk biochars. They found 0.01M CaCl2 extractable Cd was only modestly reduced in some soils treated with tamarisk biochar at application rates of 10% w/w (i.e.…”
Section: Immobilisation By Biocharsupporting
confidence: 80%
“…Considering that recent work has demonstrated how higher pyrolysis temperatures produce biochars with greater metal sorption capacity (Rodríguez-Vila et al 2017), it may be that employing biochars produced at 550°C (which would have greater sorption capacity than those used in the present study) could overcome this theorised mobilisation effect. Hypotheses aside, the results appear comparable with those of Ippolito et al (2017) who observed varying degrees of success in reducing extractable Cd in mine contaminated soils treated with pine and tamarisk biochars. They found 0.01M CaCl2 extractable Cd was only modestly reduced in some soils treated with tamarisk biochar at application rates of 10% w/w (i.e.…”
Section: Immobilisation By Biocharsupporting
confidence: 80%
“…In sandy acidic soil, increases of exchangeable/ soluble faction F1 were observed. Ippolito et al [39] showed that with increasing application rates of biochar, zinc tended to decrease in the residual fraction and increase in the soluble/exchangeable/carbonate fraction.…”
Section: Discussionmentioning
confidence: 99%
“…The PC and PL biochars were available commercially. Lodgepole pine (Pinus contorta) chips were transformed into biochar using a two-stage process as described [36]. In the first stage of the pyrolysis process, the chips were exposed to temperatures between 500 and 700 • C for <1 min under a very low O 2 atmosphere.…”
Section: Designer Biochar Preparation and Characterizationmentioning
confidence: 99%